SUSTAINABLE DEVELOPMENT PERSPECTIVES OF ROMANIAN JUSTICE SYSTEM IN THE 2030 AGENDA CONTEXT - HULPUȘ Ioana; HULPUȘ Alexandru (Management of Sustainable Development, 2023)
Sustainable development represents a new paradigm about the functioning of society, an approach that involves peaceful societies where the benefits are accessible to all. In addition, this context promotes access to justice for all and the creation of effective, accountable, and inclusive institutions at all levels. Analyzing mainly the social dimension, the paper investigates the contribution of justice in the sustainable development approach, comparing from several perspectives the progress made by Romania in the context of joining the UN 2030 Agenda and supporting the implementation of the set of 17 SDGs. Starting from the consideration that ODD 16 is one of the most innovative aspects of the sustainable development framework, we propose an analysis of the efforts to improve the quality of judicial services in accordance with the National Strategy of Sustainable Development.